The status of rubella IgG antibody titer between antenatal and postnatal among pregnant non-immune to rubella - Irfana Rasool; Ayesha Azad; Saeed Baradwan; Muhammad Salman Bashir; Dania Al-Jaroudi (Taylor & Francis Group, 2021)
Background: The infection of rubella in pregnancy is worrisome due to the fact that it causes miscarriages, congenital defects, and Congenital Rubella Syndrome (CRS). The purpose of this study was to determine the status of Rubella IgG antibody levels both during the antenatal and postnatal periods among pregnant women nonimmune to rubella and the incidence of exposure to rubella in pregnancy. Methods: This was a prospective cohort study that included 4770 pregnant, who attended the obstetric clinics and delivered in Women's Specialized Hospital, King Fahad Medical City, between January and December 2015. The study utilized the following measures for rubella screening tests (IgG and IgM) during the antenatal and postnatal period. Pregnant women with recent rubella infection (IgM antibody positive), history of rubella infection, or had immunity against rubella (IgG antibody concentration ≥10 IU/ml) were excluded from the study. Results: The prevalence of pregnant women nonimmune to rubella was 6.3% (n = 301). The majority (93.7%) were immune (IgG antibody concentration ≥10 IU/ml). No patients tested positive for rubella (IgM +ve). Overall, The Median (IQR) Rubella (IgG) in the antenatal period (6.3 (8.30-5.00) IU/m) was significantly less in comparison to the postnatal period (5.0 (6.40-5.00) IU/m). The difference was statistically significant, p <.001. Conclusion: There is a significant decrease in the Rubella (IgG) titer between antenatal and postpartum periods, and we report a very low incidence of rubella infection and CRS among pregnant women nonimmune to rubella.